2022
DOI: 10.5194/egusphere-egu22-6055
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

InSAR-based characterization of rock glacier kinematics in the La Sal Mountains, Utah, USA

Abstract: <p>Rock glaciers are perennially frozen bodies of ice and poorly sorted rock debris that flow downslope due to basal shear and deformation of interstitial ice. As common features in high mountain environments, rock glaciers constitute an important component of alpine hydrology and landscape evolution through release of seasonal meltwater and transport of debris downslope. Here, we use satellite-based interferometric synthetic aperture radar (InSAR) from 2015 to 2021 to identify and characterize r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hydrologic studies employing a paired watershed approach demonstrated increased surface runoff from basins containing rock glaciers, emphasizing that rock glaciers can act as impervious surfaces that effect downstream hydrographs (Geiger et al, 2014). Finally, optical and radar remote sensing have identified >40 active and transitional rock glaciers throughout the range, and revealed that they are moving several cm each year (Johnson et al, 2021;Kluetmeier et al, 2022).…”
Section: Settingmentioning
confidence: 99%
“…Hydrologic studies employing a paired watershed approach demonstrated increased surface runoff from basins containing rock glaciers, emphasizing that rock glaciers can act as impervious surfaces that effect downstream hydrographs (Geiger et al, 2014). Finally, optical and radar remote sensing have identified >40 active and transitional rock glaciers throughout the range, and revealed that they are moving several cm each year (Johnson et al, 2021;Kluetmeier et al, 2022).…”
Section: Settingmentioning
confidence: 99%